Real-Time Data Streaming: Advancing Technologies, Future Trends, and Industry Applications - Rajkumar Sekar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time data streaming has emerged as a transformative technology reshaping how organizations process and analyze information in the digital age. This article examines the recent advancements, current landscape, and future evolution of real-time streaming technologies across various industries. The article explores the convergence of cloud-native platforms, edge computing, and 5G networks, highlighting their collective impact on data processing capabilities. The integration of artificial intelligence and machine learning has enhanced real-time analytics and autonomous decision-making capabilities, particularly in predictive maintenance and performance optimization. It investigates implementations across healthcare, financial services, and retail sectors, demonstrating significant improvements in operational efficiency and customer experience. Furthermore, the article addresses critical challenges in security, privacy, scalability, and latency management while examining emerging trends in edge-to-cloud architectures and blockchain integration. It indicates that real-time streaming technologies will continue to play a pivotal role in driving digital transformation and enabling innovative applications across industries.
Keywords: Real-time Data Streaming; Edge Computing; Artificial Intelligence; Blockchain Integration; Cloud-Native Architecture